Assessment of middle ear risk index in predicting the outcome of treatment of CSOM - Harugop, Anil S.; Abhilasha, Somashekhar; Desai, Pratibha S. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Chronic suppurative otitis media (CSOM) accounts for highly prevalent and serious health problems especially in developing countries. Even though there are good numbers of studies demonstrating the success rate of the procedures to treat CSOM, there is lack of uniformity in assessing the predictors for the outcome of the same. If we can predict the outcome of the surgical procedure depending upon the pathologic condition of the middle ear, the cost effectiveness of the surgery can be improved, and this will also improve the patient’s compliance. The objective of this study is to evaluate a group of patients who underwent surgical treatment for chronic CSOM with reference to the prognostic significance of Middle ear risk index (MERI). Methods: It is a retrospective observational study of patients who underwent surgical treatment for CSOM from the year 2008 to 2020. Results: Out of 1010 surgeries done, total of 287 cases were included in study. In our study the success rate in mild risk index was 76.9%, moderate was 62.2% and only 18% in severe risk index. Conclusion: The outcome of surgery in the patients who undergo surgical treatment for CSOM can be predicted well using MERI. Presence of cholesteatoma and granulation tissue reduces the favourable outcome of surgery justifying the numerical value given in the score. However, presence of ear discharge and history of smoking doesn’t alter the outcome of surgery as long as complete clearance of disease is done.